From the Boarding Schools : Apache Indian Students Speak - Krupat, Arnold (Book collections on Project MUSE., 2023)
"Arnold Krupat's From the Boarding Schools makes available previously unheard Apache voices from the Indian boarding schools. It includes selections from two unpublished autobiographies by Sam Kenoi and Dan Nicholas, produced in the 1930s with the anthropologist, Morris Opler, as well as material by and about Vincent Natalish, a contemporary of Kenoi and Nicholas. Natalish was one of more than one hundred Apaches taken from Fort Marion to the Carlisle Indian School by its superintendent, Captain Richard Henry Pratt, in 1887. A considerable number of these students died at the school, and many who were sent home for illness or poor health did not recover. Natalish, however, remained at Carlisle and graduated in 1899. He married, had a son, and lived and worked in New York. He also actively sought the release of his relatives and other Apaches held prisoner at Fort Sill, Oklahoma. Apache people have been telling and circulating stories among themselves for generations. But in contrast to their neighbors the Hopis and the Navajos, Apaches have produced relatively few written autobiographical narratives, and even fewer about their boarding school experiences. Supplementing the narratives with detailed cultural and historical commentary, From the Boarding Schools brings these lived experiences from the archives into current discourse. "--